Experimental and theoretical insights in the alkene-arene intramolecular π-stacking interaction - Corne, Valeria (2016)
Chiral acrylic esters derived from biomass were developed as models to have a better insight in the aryl-vinyl π-stacking interactions. Quantum chemical calculations, NMR studies and experimental evidences demonstrated the presence of equilibriums of at least four different conformations: π-stacked and face-to-edge, each of them in an s-cis/s-trans conformation. The results show that the stabilization produced by the π-π interaction makes the π-stacked conformation predominant in solution and this stabilization is slightly affected by the electron density of the aromatic counterpart.